Japanese bunkhouse' at Whaler's Cove - Albert Walton DeRome:::Creator::::::::::::
Japanese bunkhouse' at Whaler's Cove in later years, probably near end of the Kodane abalone canning operation. Lampara fishing boats in water. The photographer, Albert Walton DeRome (Al Aagard), was a cousin of Carol Henning Steinbeck. (see Steinbeck Studies 15.1 (2004): 18.)